MySQL for beginners : a complete training. (Manning Publications, 2023)
Knowing how databases work is a considerable benefit in every career path, whether you are interested in marketing, account management, research programming, or countless other fields. Even more valuable is knowing how to design and build databases, how to query them and analyze the output. In this course you will learn all this, using the popular MySQL database management system. You will be guided through the basics of the SQL query language and introduced to MySQL databases, and then you will practice making queries. By the end of the course, you will be confident creating and managing a database. MySQL is very fast and compact, so you can run it alongside your other applications on a laptop or desktop.Yet it is a powerful and valuable tool for the many data-driven tasks that need completing. Let's get started!.